System Identification for a Mathematical Model of DC Motor System - Nur Naajihah, Ab Rahman; Nafrizuan, Mat Yahya (IEEE, 2022)
This project compares the performance of a DC motor PI-PD controller with and without a pole-zero system identification method. Cohen-Coon tuning is used to fine-tune the proposed controller’s parameters. In addition, a small number of tests were performed with varying pole and zero values. The DC motor’s performance with a PI-PD controller was evaluated throughout these tests for transient response characteristics. At the end of the study, it can be concluded that system identification is required in order to enhance the performance of the DC motor. By that, the DC motor with the PI-PD controller performed better than other variants, with 0.067s rising time, 1.748s settling time, 1.170s peak time, and 42.143 percent overshoot with no steady-state error, despite having only two poles and no zeros in the proposed controller.